Discussion on the Effect of Green Exhibition Concept on Resource Management Optimization of Hotel Industry - Liang Xiwen (SHS Web of Conferences)
With the increasing global awareness of environmental protection, the concept of green exhibition has gradually become one of the important ways for the hotel industry to pursue sustainable development. The purpose of this paper is to explore how the concept of green exhibition promotes the optimization of resource management in the hotel industry, and to deeply analyze its positive effects from multiple perspectives through the combination of theoretical analysis and case study. First, based on Principles of Economics and Principles of Management, we explain the basic concept of green exhibition and its importance in improving the efficiency of resource utilization. Then, combined with the views of “Tourism Economics”, the contribution of green exhibition activities to promoting the overall sustainable development of tourism is discussed. In addition, the paper also introduces in detail the specific application of green exhibition practice in the hotel industry, including but not limited to energy conservation, green service innovation, etc., and demonstrates the practical effects of these measures through the cases provided by International Hotel Management Research. Further, this paper puts forward optimization strategies for material procurement, human resources allocation and customer experience, in order to provide operable suggestions for hotel managers. Finally, through the summary of the existing challenges and the prospect of future trends, the importance of continuing to explore the green exhibition model for the long-term development of the hotel industry is emphasized. This study not only enriches the academic discussion in related fields, but also provides valuable reference for practitioners.